The impact of monetary policy instruments on sustainable development - Jothr, Osama Abdulsalam; Jummaa, Ahmed Ibriheem; Didik Kusno Aji. N; Ambariyani, Ambariyani (CV. Bimbingan Belajar Assyfa, 2023)
In this research, the effect of monetary policy on five sustainable development indicators prepared by the United Nations was investigated in Iraq. For this purpose, variables of interest rate, exchange rate and volume of money in circulation have been used as monetary policy tools and the indicators have been used such as Proportion of the population living below the international poverty line (1.1.1), Proportion of population using safely managed drinking water (6.1.1.), Change in water-use efficiency (6.4.1), Renewable energy (7.2.1), share in the total final energy consumption, and Annual growth rate of real GDP per capita (8.1.1.). For this purpose, five regressions were estimated using the Two Stage Least Squares (2SLS) method. The results show that the exchange rate has a positive effect on indicators of poverty, efficient management of water resources, and economic growth per capita, and a negative effect on access to safe drinking water. Among other monetary policy instruments, only currency in circulationhas a positive effect on poverty reduction, and in other cases it has no significant effect.